How spatial planning can enable pathways toward wildfire mitigation within the fire-prone wildland and urban interface, City of Cape Town - Pieters, Ewan (School of Architecture, Planning and Geomatics, 2023)
18th of April 2021, a wildfire raged through parts of the University of Cape Towns upper campus, with damage assessed at approximately R500 million. There were calls from senior leadership that UCT "will rebuild facilities". The post-disaster rhetoric of rebuilding is problematic, as we should never rebuild what was because the old geographic, economic and social position is no longer sustainable. Critical disaster management frameworks strongly advocate more emphasis on preventing disasters; without compromising the much-needed reactive qualities of the discipline. It places responsibility on spatial planning – development restrictions, land uses, building regulations, tenure boundaries, spatial layout and road patterns –as the critical juncture toward achieving long-term disaster risk reduction. Due to climate change, wildfire anomalies and associated destructiveness oblige humankind to revise pieces of knowledge calibrated to conditions that no longer exist. This research responds to this call for "different ways of thinking", investigating the local merging of planning and disaster disciplines in hopes of creating new knowledge to realise longterm wildfire risk reduction within flammable Wild and Urban Interface, City of Cape Town. This qualitative dissertation collected primary data using online semi-structured interviews with local spatial planners, engineers, disaster management officials and insurance brokers. Secondary data was collected through a review of published journals; and regulations and policies from California, Victoria and Western Cape. Both data sets are used to investigate spatial planning as leverage to realise long-term wildfire risk reduction for the University of Cape Town and Spanish Farm Somerset West sites (the case studies of the dissertation). Even the best firefighting equipment will not help much during an extreme weather wildfire due to ember storms making fire breaks redundant. Fire-fighting and suppression technologies are less effective than perceived during wildfire extreme weather events. When it comes to traditional wildfire disaster measures such as prescribed burnings and alien vegetation removal – locally, these mitigation techniques are well established. However, the study found that disaster management respondents and best practice policy analysis, local and abroad, unanimously agree that focus must be placed on protecting urban structures for overall wildfire risk reduction. The study found that local planners and disaster management officials rarely collaborate on wildfire disaster matters due to misaligned goals and ideals. In the context of climate change, the study found that the local zoning scheme needs an overlay zone dedicated fully to wildfire mitigation, as local overlays have the unique ability to guide development in a potential "fire-safe manner". Within the City of Cape Town, spatial planning has the unique potential to realise this focus through an amended provincial zoning scheme. The study proposes a Western Cape veld and forest fire management overlay zone that demarcates high-fire risk regions on the urban edge, pre and post-development. The proposed overlay imposes restrictions on these sites to bypass "rebuilding" unsustainably and initiate "build back better" post disaster. This theorises a wildfireresilient City of Cape Town wild land urban interface. The study employs this proposed fire-specific overlay zone over the projects case studies (UCT and Spanish Farm) – to show how it could potentially mitigate wildfire risk in these flammable sites. The basis of this idea is formed from a cross-contextual analysis of Victoria, California and Western Cape regulation; and from the insights of planning, engineer, wildfire disaster management and insurance industry respondents from the Western Cape region.